2012
DOI: 10.1029/2011jg001810
|View full text |Cite
|
Sign up to set email alerts
|

Using the deuterium isotope composition of permafrost meltwater to constrain thermokarst lake contributions to atmospheric CH4 during the last deglaciation

Abstract: [1] Thermokarst lakes are thought to have been an important source of methane (CH 4 ) during the last deglaciation when atmospheric CH 4 concentrations increased rapidly. Here we demonstrate that meltwater from permafrost ice serves as an H source to CH 4 production in thermokarst lakes, allowing for region-specific reconstructions of dD CH4 emissions from Siberian and North American lakes. dD CH4 reflects regionally varying dD values of precipitation incorporated into ground ice at the time of its formation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
87
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(95 citation statements)
references
References 117 publications
8
87
0
Order By: Relevance
“…There is no indication of HM, which has a very different isotope signature, although the signature of samples collected from the center of lakes tend to lie towards the HM region, suggesting that a small proportion of the CH 4 produced could be through this pathway. This finding of AM dominance is consistent with ombrotrophic bogs with higher pH (ranging from ∼ 6.7 to 10.0 in 2014) compared with more acidic minerotrophic wetlands, which can be HM dominated (e.g., Bowes and Hornibrook, 2006;Prater et al, 2007). The dominance of AM is likely related to the carbon precursors; our sites may have more labile organic material present (e.g., organic acids) supporting acetoclastic methanogenesis and recently made available to methanogens.…”
Section: Production Pathways Of Co 2 and Chsupporting
confidence: 72%
See 1 more Smart Citation
“…There is no indication of HM, which has a very different isotope signature, although the signature of samples collected from the center of lakes tend to lie towards the HM region, suggesting that a small proportion of the CH 4 produced could be through this pathway. This finding of AM dominance is consistent with ombrotrophic bogs with higher pH (ranging from ∼ 6.7 to 10.0 in 2014) compared with more acidic minerotrophic wetlands, which can be HM dominated (e.g., Bowes and Hornibrook, 2006;Prater et al, 2007). The dominance of AM is likely related to the carbon precursors; our sites may have more labile organic material present (e.g., organic acids) supporting acetoclastic methanogenesis and recently made available to methanogens.…”
Section: Production Pathways Of Co 2 and Chsupporting
confidence: 72%
“…Another important yet rarely considered aspect is the age (old vs. modern) of the carbon that is processed and released by these biogeosystems, which is linked to their potential to generate a positive feedback on climate Mann et al, 2015). Large GHG emissions (especially CH 4 ) from old (late Pleistoceneage) organic ice-rich loess permafrost (yedoma) have been reported from thermokarst lakes of Siberia and Alaska in regions that were not ice-covered during the last glaciation (Zimov et al, 1997;Brosius et al, 2012). In Canada, which accounts for a very large portion of circum-Arctic permafrost, these deposits are rare as the territory was almost entirely covered by ice sheets during that period (Dyke and Prest, 1987).…”
Section: F Bouchard Et Al: Ghgs Emitted From Ponds and Lakes Of Thementioning
confidence: 99%
“…Therefore, the age of the studied lake basin ranges between about 11,200 and older than 5000 cal yrs BP, the latter being the oldest date obtained in the present record. This is supported by a peak in basal ages of thermokarst lakes in northwest Canada and Alaska during the Holocene thermal maximum (Rampton, 1988;Brosius et al, 2012).…”
Section: Stage 1: Thermokarst Lake Stage (!4950 To 3950 Cal Yrs Bp)mentioning
confidence: 61%
“…Their lifetime e in contrast to the onset e largely depends on local factors such as geomorphology, ground-ice conditions, hydrology and groundsurface stability (Jones et al, 2011(Jones et al, , 2012Jones and Arp, 2015). The initiation of many thermokarst lakes in northwest Canada, Alaska, and Siberia is related to increasing air temperatures, available moisture and permafrost thaw in response to short-term warming events during the Pleistocene-Holocene transition or later on during the Holocene thermal maximum (Rampton, 1988;Brosius et al, 2012;Walter Anthony et al, 2014). However, Burn and Smith (1990) noted that such lakes may also develop in response to site-specific factors such as ground disturbance, which are not necessarily related to regional climatic change.…”
Section: Thermokarst and Thaw Lake Dynamicsmentioning
confidence: 99%
“…Many of the studies to date have focused on the greenhouse gas emission potential of large lakes such as thermokarst lakes (Zimov et al, 1997;Walter K. M. et al, 2006;Brosius et al, 2012). However, recent studies have demonstrated that not only large Arctic lakes, but also the smaller Arctic ponds, are hotspots of CO 2 and CH 4 emission (Abnizova et al, 2012;Laurion et al, 2010).…”
Section: Langer Et Al: Frozen Pondsmentioning
confidence: 99%